Evaluation of the Effect of Capacitor Banks on Energy Efficiency in The 20 kV Distribution System at PT. Unilever Oleochemical Indonesia (UOI) - Jamil Alfasyah; Rahmaniar, Rahmaniar; Siti Anisah (INFOKUM, 2025)
Enhancing energy efficiency in industrial electrical distribution networks is a strategic imperative amid rising power consumption. This study simulates the impact of capacitor bank installation on power factor improvement and power loss reduction within a 20 kV medium-voltage distribution system that reflects the load profile of chemical industries, particularly at PT. Unilever Oleochemical Indonesia (UOI). A numerical simulation method is applied using reactive power calculations across load variations (800–1200 kW), implemented via scientific programming techniques. Results indicate a consistent improvement in power factor from 0.78 to 0.95, alongside a system loss reduction exceeding 700,000 relative units. Validation is conducted through comparative analysis with high-impact literature and national standards. This research offers a substantial contribution as a decision-making foundation for energy efficiency strategies in industrial sectors, promoting the adoption of reactive power compensation technologies.